Effect of Egg Disinfection by Silver Nanoparticles on Eggshell Microbial Load, Hatchability and Post-hatch Performance of Quail Chicks - Ibrahim, Faten A.; El.Mousafa , Kout Elkloub M.; El Sabry, M.I.; Badr, Jihan M.; Hassan, A.S.I. (International Journal of Poultry Science, 2018)
Background and Objective: Sanitation improvement of fertile eggs is an important point of research, as it is the goal of selection of the hygiene programs in commercial hatcheries. Silver nanoparticles (Ag-NPs) have new physical and chemical characteristics enabling it to have a strong antibacterial activity. This study was aimed to evaluate the effect of different concentrations of Ag-NPs as a disinfectant, on a microbial load on the quail eggshell, embryonic mortality, hatchability, chick quality and post-hatch performance. Methodology: Silver nanoparticles were synthesized and characterized by UV, concentration and transmission electron microscopy (TEM). A total of 1920 fertile quail eggs were randomly divided into 4 treatment groups, one control group disinfected by spraying with a commercial disinfectant (TH4) and three treated groups sprayed with 30, 40 or 50 ppm of Ag-NPs. Thirty minutes after spraying, eggs in each group were sampled for determination of total bacterial and total coliform counts. Results: Results showed that bacterial loads on the eggshell were declined with the elevation of the concentration of Ag-NPs used. The 50 ppm concentration of Ag-NPs had the lowest bacterial load. Also, hatchability of the treated groups was increased by increasing Ag-NPs concentration. Hatchability of Ag-NPs 50 group was higher than the control group (p<0.05). Embryonic mortality rates were decreased by increasing Ag-NPs concentration. Chick weight, length and quality of all Ag-NPs treated groups were numerically greater compared to the control ones. Performance of post-hatching quails constituted by body weight (BW), body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) for all investigated groups was similar. Moreover, treatments had no negative effect on the structure of the liver. Conclusion: In conclusion, using Ag-NPs at different concentration (30, 40 and 50 ppm) in disinfecting quail embryonated eggs can effectively reduce bacterial load on eggshell. Also, using 40 ppm of Ag-NPs improved hatchability and chick quality without any adverse effect on the liver structure.